Analysis of the use of media resulting from bioconversion of organic waste in the production of maggots BSF (black soldier fly) - Syahrizal syahrizal; Ediwarman; Safratilofa; Muhamat Ridwan (Jurnal Akuakultur Indonesia)
Maggots is an organism derived from the eggs of the black fly, Hermentia illucens (black soldier fly, BSF), which undergoes metamorphosis in the second phase after the egg phase and before the pupa phase which then turns into an adult fly. The purpose of this study was to analyze the utilization of organic waste substrate on the production of BSF maggots cultivation. This research was conducted outdoor at the Freshwater Aquaculture Fisheries Center (BPBAT) Sungai Gelam Jambi with a completely randomized design (CRD) with 4 treatments and 3 replications; Treatment A: PKM (palm kernel meal) 100%, B (PKM 50% + cabbage vegetable waste 50%), C (PKM 50% + coconut pulp 50%) and D (PKM 50% + coconut pulp 25% + vegetable waste cabbage 25%). The average yield parameter of high maggots biomass in treatment A was 673.67 g/4 kg substrate and the lowest biomass in treatment D was 239.67 g/4 kg substrate. For the average weight and length of the best maggots in treatment A (0.20 g/individual) and (1.83 cm), the lowest was in B (0.12 g/Ind. and 1.58 cm). The highest was in treatment B (5,182.31 individual/4 kg substrate) and the lowest was in D (1,479.44 ind./4 kg substrate. The highest bioconversion value of maggots to organic matter OSE (organic substrate efficiency) was highest in treatment A (16, 84%) and the lowest was in D (5.99%). Technically, treatment A was slightly better than B, while economically the best organic substrate medium for maggots cultivation was in treatment B with a production cost of Rp. 7.257 and the ECR (economic conversion ratio) value of 5.81 was lower than the other 3 treatments.